Overweight, Obesity and its Associated Factors among Nurses at Tertiary Care Hospitals Karachi: Overweight, Obesity and its Associated Factors - Ali, Junaid; Badil, .; Raja, .; Sami, Farina; Ali, Yasir; Ali, Sajid; Qadir, Ghulam (Pakistan Journal of Health Sciences, 2023)
Overweight and obesity have been identified as considerable health risks worldwide. Objective: To identify the prevalence of overweight, and obesity and its association with demographic variables among nurses. Methods: A cross-sectional analytical study was conducted at Dr. Ruth KM Pfau Civil Hospital and Dow University Hospital Karachi over a period of six months of periods from March to August 2019. A total of 299 subjects of both genders were approached by the non-probability convenient sampling method. Chi-square test was applied to identify the associated factors. P-value ≤ 0.05 counted as significant. Results: Out of 299, half of the study nurses 149 (49.8%) were male. Among 299 participants, 75 (25.1%) of them were overweight or obese. While 13 (4.3%) were underweight and 211 (70.6%) were normal weight. Mean age, working experience, and BMI were found 29.52 ± 8.568, 7.35 ± 6.177, and 23.30 ± 3.148 respectively of the study nurses. Gender (p-value=0.003), educational status (p-value=0.002), and nature of the job (p-value=0.003) of the participants were found statistically significant with BMI. Conclusions: Present study concluded that the majority of study participants had normal BMI and a small number of study subjects were found obese. However, a quarter of nurses are recognized as overweight. Moreover, a significant association was established between BMI with gender, the nature of the job, and the education of nurses.